2009
DOI: 10.3899/jrheum.090667
|View full text |Cite
|
Sign up to set email alerts
|

Signs of Accelerated Preclinical Atherosclerosis in Patients with Ankylosing Spondylitis

Abstract: AS was associated with subclinical atherosclerosis and arterial stiffness, supporting epidemiological evidence of an increased CV risk in these patients. Whether these differences are due to AS or to a higher prevalence of CV risk factors in patients with AS remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
45
2
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 31 publications
11
45
2
5
Order By: Relevance
“…Peters et al 18 also detected that CIMT did not show any association with BASDAI in AS patients. Angel et al 16 demonstrated that impairment in aortic elasticity occurs independently of disease activity in subjects with AS.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Peters et al 18 also detected that CIMT did not show any association with BASDAI in AS patients. Angel et al 16 demonstrated that impairment in aortic elasticity occurs independently of disease activity in subjects with AS.…”
Section: Discussionmentioning
confidence: 95%
“…11 Several studies showed that patients with AS exhibited greater CIMT. [12][13][14] and ASI [15][16][17][18] than healthy controls. However, no studies have been performed regarding the association between AS patients and EFT.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Still, the current evidence base for a link between AS and CV disease is limited. 8,19 However, current data suggest that inflammation has a role in the development of endothelial impairment, and chronic inflammation leads to accelerated atherogenesis, particularly in rheumatoid arthritis and AS. 20 Pulse wave velocity is a marker for vascular dysfunction and an independent risk factor for CV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Одна из основных причин леталь-ности при АС -ССЗ [17][18][19]. Так же как и при РА, ФР ССО при АС являются дислипидемия [20], повышенная распро-страненность АГ [17,21], СД 2-го типа [17], увеличение толщины комплекса интима -медиа или наличие АТБ [22][23][24]. Кроме того, отмечено увеличение частоты неате-росклеротических ССЗ (патология аортального клапана и нарушение проводимости).…”
Section: общие принципыunclassified